2018
DOI: 10.4236/ojpsych.2018.81007
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Non-Disclosure in Psychiatric Patients from a Southeast Asian Hospital

Abstract: Objective: We compared stigma experienced by psychiatric patients and controls in various social domains and hypothesized higher levels of stigma and higher rates of non-disclosure by psychiatric patients. Methods: Psychiatric outpatients and a control group of medical outpatients were assessed for experienced discrimination through a structured questionnaire that included adapted items from the Discrimination and Stigma Scale (DISC-12). Controls were assessed on discrimination related to physical, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…10,14 It was reported that marriage had a positive effect on psychiatric patients’ self-esteem, with the view that spouses provided emotional support, thus mitigating the effect of stigma. 15 Our present data also suggested that older subjects had better self-esteem and was consistent with other studies, which demonstrated increase in self-esteem with age. 16 Our present findings also seemed to suggest that religious affiliation conferred beneficial effects on self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…10,14 It was reported that marriage had a positive effect on psychiatric patients’ self-esteem, with the view that spouses provided emotional support, thus mitigating the effect of stigma. 15 Our present data also suggested that older subjects had better self-esteem and was consistent with other studies, which demonstrated increase in self-esteem with age. 16 Our present findings also seemed to suggest that religious affiliation conferred beneficial effects on self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…Further, the lack of association between DSH and a positive family history of psychiatric disorder may also be attributed to the lack of accurate report from the adolescent patient. Because of the stigma and common misperceptions towards mental illness in Singapore, many individuals cope by withholding information to avoid discrimination [ 28 ]; this may mask the presence of mental illness in some families. Future studies would benefit from the use of more sensitive indicators to investigate DSH and its associations with social and familial stressors and supports.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) states that mental disorders affect one in four people but psychiatric conditions are still considered as “not normal”, or somewhat deviant from the norm in most societies, and many people are ashamed to have mental health issues. For this reason a high proportion of psychiatric patients practise non-disclosure of their illness [ 4 ].…”
Section: Introductionmentioning
confidence: 99%